A vibrant stage for talent: Open Mic Nights at UiTMCPP / Noor Azli Affendy Lee - Affendy Lee, Noor Azli (Academy of Language Studies, 2024)
Open Mic Nights 2024 are more than just evenings of entertainment— they are vibrant celebrations of creativity and community. Held monthly, these events transformed “The Brick" café at Universiti Teknologi MARA Penang Branch (UiTMCPP) Permatang Pauh Campus into a lively hub where students gather to express their talents and share their stories. Organised by the English Language Club, the sessions in April, May, and June 2024 have left a lasting impact on both participants and audiences alike.